Pluralisation des savoirs et cultures minoritaires - Nathalie Casemajor; Stéphane Couture (Revue d'anthropologie des connaissances)
This article studies the cultural and political issues of the knowledge pluralization in Wikipedia.fr. It analyzes the case of the Franco-Ontarians portal as an example of the representation of a French-speaking minority within the encyclopedia. Although several works exist on the linguistic and cultural dimensions of Wikipedia, few studies examine the place of a minority group within a single language edition of Wikipedia. The analysis first shows how the Franco-Ontarian identity is represented in the portal, and who the portal's contributors are. It then identifies points of tension about the legitimacy of minority cultures in the encyclopedia, tensions related both to the modalities of internal governance and to issues of broader political recognition. The article contributes more generally to the conceptual development of the notion of knowledge pluralization by linking it with the notions of minority, identity and cultural expression